Spiritual well-being and quality of life in maintenance hemodialysis patients: a latent profile analysis and serial mediation model - Yuan, BiXia; Lai, QingHua; Wu, Jing; Wang, RongRong; Lu, YongMei; Wu, Meng; Chen, Yun; Wu, JieQian (Frontiers in Psychology, 2026)
BackgroundFrom a positive psychology perspective, this study aimed to identify the latent profiles of spiritual well-being and analyze the serial mediation mechanism of family care and spiritual coping in the relationship between spiritual well-being and health-related quality of life (HRQoL). The findings are intended to inform strategies for improving the spiritual well-being of maintenance hemodialysis (MHD) patients.MethodsA cross-sectional design was employed with 220 MHD patients recruited from two tertiary hospitals in Guangdong, China (August 2023–January 2024). Assessments were conducted using the Functional Assessment of Chronic Illness Therapy–Spiritual Well-Being Scale (FACIT-SP-12), Family Care Index, Spiritual Coping Questionnaire (SCQ), and Short Form-12 Health Survey (SF-12). Latent profile analysis (LPA) was employed to identify heterogeneous subgroups based on spiritual well-being. A chain mediation model was then used to examine the mediating effects of family care and spiritual coping.ResultsHRQoL scores averaged 56.50 ± 22.29. Significant correlations emerged: spiritual well-being (r = 0.557, p < 0.001), family care (r = 0.426, p < 0.001), and positive spiritual coping (r = 0.565, p < 0.001) positively predicted HRQoL, whereas negative coping correlated inversely (r = −0.343, p < 0.001). LPA identified four distinct profiles: Low spiritual well-being (36.8%), Moderate spiritual well-being (20.0%), Peaceful Mindset with Low Spiritual Belief (13.6%), and High spiritual well-being (29.5%). The mediation analysis revealed that family care and spiritual coping partially mediated the relationship between spiritual well-being and HRQoL (effect sizes: 0.074–0.175, 95% CI excluding 0). The chain mediation pathway “spiritual well-being → family care → spiritual coping → HRQoL” was statistically significant, with total indirect effects of 0.268 and 0.114 (95% CIs excluding 0).ConclusionSpiritual well-being indirectly influences the quality of life in MHD patients through the serial mediation of family care and spiritual coping. Clinicians should recognize the heterogeneity in spiritual well-being and integrate routine spiritual screening into nursing assessments to identify patients with low spiritual well-being. It is recommended to develop family-based education and support programs, along with interventions that combine family care and spiritual coping strategies, so as to improve patients’ long-term health outcomes.